MASALAH-MASALAH DALAM PEMBELAJARAN MATEMATIKA - Priyo Utomo, Dwi (Widya Warta, 2011)
The problems described are common problems that occur in learning mathematics in secondary school. The problems that occur can be grouped according to the learning component, i.e., materials, methods, media, evaluation, and classroom management. The problems associated with learning material are the tendency of teachers to immediately resolve the learning materials from the achievement of understanding and avoid the problem solving and geometry. The issues relating to the learning method are that: (1) the method used is less closely linked with the experience of everyday life, (2) information is too obvious, (3) there are rarely teachers who apply the learning with group work, (4) teachers emphasize drills rather than develop the power of reason, and (5) teachers ask students to memorize formulas. The problems associated with the media are concerned with the use of visual aids by the students. The issues relating to evaluation are dealt with the fact that evaluation is always convergent. The problems associated with management of the class are that seating arrangements and room seem to be rather stiff.